The relationships between teachers’ emotional labor and display rules, trait emotions, exhaustion, and classroom emotional climate - Ma, Pei; Zhang, Lichang; Dong, Hui; Yu, Jian (Frontiers in Psychology, 2023)
Emotions are an integral part of education, and the way teachers manage their emotions is crucial to educational success. This study focuses on teachers’ emotional labor in secondary school classrooms and examined the relationships between the strategies and display rules, trait emotions, emotional exhaustion, and classroom emotion climate. In the study, 496 secondary school teachers (386 women) aged 21–59 years (Mean age = 37.61 ± 8.87 years) completed five self-reported questionnaires. Data were analyzed using structural equation model in AMOS. Results showed that (1) display rules provide positive situation to deep acting and the expression of naturally felt emotions, and mediate teachers’ positive emotions and strategies; (2) positive trait emotions increase the expression of naturally felt emotions, and negative trait emotions increase surface acting; (3) surface acting results in emotional exhaustion and has an adverse impact on classroom emotional climate; and (4) deep acting and the expression of naturally felt emotions positively affect classroom emotional climate. These findings revealed that deep acting and the expression of naturally felt emotions are positively related to positive emotions and the classroom setting, whereas surface acting plays a negative role in the emotional states of individuals and the classroom. The study gives centrality of teacher emotions in teaching and learning process, clarifies some antecedents and consequences related to emotional labor strategies in classroom setting and provides some ideas to optimize educational outcomes. The five variables presented in the study are good examples that can contribute to protecting teachers’ well-being and improving the psycho-sociological environment.